Activating cobalt(II) oxide nanorods for efficient electrocatalysis by strain engineering - Ling, Tao; Yan, Dong-Yang; Wang, Hui; Jiao, Yan; Hu, Zhenpeng; Zheng, Yao; Zheng, Lirong; Mao, Jing; Liu, Hui; Du, Xi-Wen; Jaroniec, Mietek; Qiao, Shi-Zhang (Nature communications, 2017)
Designing high-performance and cost-effective electrocatalysts toward oxygen evolution and hydrogen evolution reactions in water–alkali electrolyzers is pivotal for large-scale and sustainable hydrogen production. Earth-abundant transition metal oxide-based catalysts are particularly active for oxygen evolution reaction; however, they are generally considered inactive toward hydrogen evolution reaction. Here, we show that strain engineering of the outermost surface of cobalt(II) oxide nanorods can turn them into efficient electrocatalysts for the hydrogen evolution reaction. They are competitive with the best electrocatalysts for this reaction in alkaline media so far. Our theoretical and experimental results demonstrate that the tensile strain strongly couples the atomic, electronic structure properties and the activity of the cobalt(II) oxide surface, which results in the creation of a large quantity of oxygen vacancies that facilitate water dissociation, and fine tunes the electronic structure to weaken hydrogen adsorption toward the optimum region. The efficiencies of materials-based catalysts are determined by the surface atomic and electronic structures, but harnessing this relationship can be challenging. Here, by engineering strain into cobalt oxide, the authors transform a once poor hydrogen evolution catalyst into one that is competitive with the state of the art.